Agonist-Induced Internalization of Serotonin-1A Receptors in the Dorsal Raphe Nucleus (Autoreceptors) But Not Hippocampus (Heteroreceptors) - Riad, Mustapha; Watkins, Kenneth C; Doucet, Edith; Hamon, Michel; Descarries, Laurent (The Journal of neuroscience, 2001)
Serotonin-1A (5-HT(1A)) receptors in the CNS are a major target for psychotropic drugs. In nucleus raphe dorsalis (NRD) and hippocampus (CA3), the selective 5-HT(1A) agonist (+)-8-hydroxy-2-(di-N-propylamino) tetralin (8-OH-DPAT) reduces the firing activity of serotoninergic (5-HT) and pyramidal neurons, respectively. When located on 5-HT (autoreceptors), but not on non-5-HT (heteroreceptors) neurons, 5-HT(1A) receptors are known to be subject to desensitization. Using quantitative electron microscopy after pre-embedding immunogold labeling with specific antibodies, we examined the subcellular distribution of these receptors after acute administration of 8-OH-DPAT (0.5 mg/kg, i.v.). Silver-intensified immunogold particles associated with the plasma membrane or the cytoplasm were counted in somata and dendrites within the NRD, 15 min, 1 hr and 24 hr after 8-OH-DPAT injection, and in hippocampal dendrites 1 hr after the same treatment. Significant decrease in the density of membrane labeling and concomitant increase of cytoplasmic labeling were demonstrated in the NRD, 15 min and 1 hr after 8-OH-DPAT administration, with a return to baseline level at 24 hr. Internalization was blocked by previous administration of the 5-HT(1A) antagonist N-[2-[4-(2-methoxyphenyl)-1-piperazinyl]ethyl]-N-(2-pyridinyl) cyclohexane-carboxamide (WAY 100635), which, by itself, was without apparent effect. In hippocampus (CA3), there were no apparent changes in the distribution of the receptor after 8-OH-DPAT administration. These findings are in line with earlier results showing a desensitization of 5-HT(1A) autoreceptors but not heteroreceptors after treatment with 5-HT(1A) receptor agonist. They suggest that this desensitization is the result of autoreceptor internalization.